2016
DOI: 10.3171/2016.3.peds1612
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of the developing pediatric cervical spine

Abstract: OBJECTIVE Our understanding of pediatric cervical spine development remains incomplete. The purpose of this analysis was to quantitatively define cervical spine growth in a population of children with normal CT scans. METHODS A total of 1458 children older than 1 year and younger than 18 years of age who had undergone a cervical spine CT scan at the authors' institution were identified. Subjects were sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 32 publications
4
20
0
Order By: Relevance
“…However, the present study showed continued growth in age cohort IV (15–20 years), supporting the findings that growth in size continues for well over 9 years (Johnson et al. ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, the present study showed continued growth in age cohort IV (15–20 years), supporting the findings that growth in size continues for well over 9 years (Johnson et al. ).…”
Section: Discussionsupporting
confidence: 91%
“…; Johnson et al. ); poor improvement over use of chronological age (Chatzigianni & Halazonetis, ), and not accounting for sexual dimorphism of the cervical spine (Caldas et al. ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 However, a morphometric study reported that the normal vertical growth of the pediatric C-spine continues up to 18 years of age in boys. 21 In the present case, 6 months after removing the cervical plate, the lateral X-rays demonstrated an improvement of the cervical curvature ( Figure 4; Table 1). In addition, there were no further clinical complaints.…”
Section: Discussionsupporting
confidence: 55%
“…A major difference between the pediatric spine and adult spine is the potential for continued growth from childhood to adolescence. 71 This growth must be factored into any decision of performing a long-segment fusion in a child. Adverse iatrogenic effects from spinal fusion include limitation of range of motion, stunting future growth, development of secondary deformity (e.g., crankshaft deformity), and adjacent-level disease.…”
Section: Long-term Consequences Of Fusion In a Growing Spinementioning
confidence: 99%